2018
DOI: 10.3390/nu10030322
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Human Intestinal Cell Lines for Studying Dietary Protein Absorption

Abstract: With the global population rising, the need for sustainable and resource-efficiently produced proteins with nutritional and health promoting qualities has become urgent. Proteins are important macronutrients and are involved in most, if not all, biological processes in the human body. This review discusses these absorption mechanisms in the small intestine. To study intestinal transport and predict bioavailability, cell lines are widely applied as screening models and often concern Caco-2, HT-29, HT-29/MTX and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 111 publications
0
32
0
1
Order By: Relevance
“…As a model of human intestinal epithelium Caco-2 cell monolayers were used. These cells derive from a human colon adenocarcinoma; once in culture they undergo a process of spontaneous differentiation into normal mature enterocytes (Jochems et al, 2018). iNOS is not usually expressed in these cells, but its expression can be induced by bacterial LPS, cytokines, and other toxic or proinflammatory agents (Förstermann & Sessa, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As a model of human intestinal epithelium Caco-2 cell monolayers were used. These cells derive from a human colon adenocarcinoma; once in culture they undergo a process of spontaneous differentiation into normal mature enterocytes (Jochems et al, 2018). iNOS is not usually expressed in these cells, but its expression can be induced by bacterial LPS, cytokines, and other toxic or proinflammatory agents (Förstermann & Sessa, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…(b) Transcellular passive diffusion involves the transport of molecules through apical and basolateral membranes in a concentration-based and energy-independent manner [ 94 ]. The transport of bioactive peptides through passive diffusion is dependent on peptide characteristics such as size, charge, and hydrophobicity [ 95 ].…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
“…Antiporters translocate peptides in opposite directions, whereas symporters transport them via cotransport in the same direction over the blood membrane. Uniporters function unidirectionally, without cotransport [ 94 ]. This transport system is dependent of susbtance concentration, susceptible to inhibition, and specific to the molecules’ structure [ 104 ].…”
Section: Bioavailability Of Food Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional foods are capable of inducing health benefits beyond their nutritional value and offer interesting candidates [ 9 ]. Proteins are often used as the backbone of complete nutritional interventions and are involved in almost all biologic processes within the human body [ 10 ]. In accordance, previous data suggested that food-derived proteins and/or protein fragments harbor functions that contribute to intestinal health, as reviewed by Martínez-Augustin et al [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%